PELATIHAN PENGOBATAN TRADISIONAL GUSMUS RAKSA JASAD UNTUK MENINGKATKAN EKONOMI MASYARAKAT DI TITIK KORDINAT DANGIANG MANILOKA - Rostikawati, Yeni Hasanah; Ansori, Ansori (IKIP Siliwangi, 2025)
Traditional medicine has become an integral part of people's culture to maintain health and balance in life. This journal proposes a study that explores the potential of traditional medicine using the gusmus raksa jasad method in improving the community's economy. Gusmus raksa jasad is a holistic approach that combines spiritual, mental and physical elements in healing efforts.This research aims to identify the positive impact of implementing the traditional treatment of gusmus raksa jasad on public health and how this can stimulate local economic growth. The research methodology involved surveys and interviews with traditional medicine practitioners, patients, as well as local economic stakeholders. The collected data will be analyzed to understand the effectiveness of traditional medicine in improving community welfare.It is hoped that the research results will provide in-depth insight into the economic potential of traditional gusmus raksa jasad medicine and support the development of policies that integrate local values with efforts to improve the economic welfare of the community. It is hoped that this research can make a positive contribution in preserving traditional healing practices and encouraging sustainable economic development at the local level.